Tahap pengetahuan, sikap dan amalan terhadap risiko kecederaan tusukan jarum dalam kalangan pelatih Institut Latihan Kementerian Kesihatan Malaysia - Mohd Zulhairi, Abd Wahab (2020)
Needle-stick injury (NSI) is not a new phenomenon, and it commonly happens among healthcare workers, including trainees. It is not only give a negative impact towards the victims but also affects the community and the country. Previous studies shown that the factors affecting the incidence of needle-stick injury include individual factors, patients, types of equipment and management. Hence, the study is carried out to explore the prevalence of needle-stick injury and the level of knowledge, attitude and practice towards the risk of needle-stick injury among the diploma trainees of Institut Latihan Kementerian Kesihatan Malaysia, Seremban. The study was carried out with quantitative approach. The data collected was analyzed with a frequency test and cross-tabulation. A total of 137 respondents were involved, and the data collected was analyzed with SPSS version 25. The frequency test revealed a high level of knowledge and attitude among respondents with a total of 100% for almost all measured items and a moderate level of practice primarily in the Universal Precaution and SOP sections. Then, the cross-tabulation demonstrated that the three factors had a positive relation and were able to affect the respondents. The study has also shown that the trainees are at high risk of NSI. It is hoped that the study will serve as a guide in making policy related to NSI and the trainees should abide by every SOP made to minimize the risk. Besides, it can potentially help to change the trainees’ perception towards the danger of NSI and will serve as a reference for future researchers in view of the few studies that were carried out on Assistant Medical Officer trainees.